Revolutionizing fashion retail through virtual try-on technology - Ahmedy, Hajar; Hussein, Nazatul Syahira; Jaini, Azila; Kamar, Madiha Badrol
The rapid growth of e-commerce and social commerce platform has redefined the way consumers interact with fashion. Nevertheless, the inability to imagine the real time product with actual body type remains a significant limitation, especially e-commerce and social commerce platform. This project introduces a Virtual try-on system specifically designed for clothing websites, offering an immersive and interactive experience to overcome this barrier. Utilizing an advanced VR technology, consumer can virtually “wear” their selected outfits in real time, enabling more informed purchasing decision through highly realistic visual simulations. Unlike traditional modes of shopping, this model provides a proactive approach designed to enhance consumer confidence, aligned with modern technological trends. Additionally, the VR Try-On system supports business growth and consumer satisfaction while preserving cultural traditions through innovative applications. Its uniqueness lies in its ability to adapt and improve over time, ensuring precise and reliable performance while minimizing inaccuracies. By offering an immersive Virtual Try-On system, this innovation enhances online shopping accuracy and reduces decision-making uncertainty, thereby decreasing product returns and enhancing customer satisfaction. The platform supports efficient resource usage, minimizes waste, and fosters sustainable business practices in the fashion industry. This project contributes to building a more resilient and innovative digital retail infrastructure, promoting seamless purchasing experience, and driving socio-economic in fashion sector.